A saúde popular comunitária e o Projeto Casa do Caminho: construindo a saúde integral com base em saberes ancestrais e decoloniais em comunidades rurais e de periferias urbanas da região sul do RS - Ferreira, Fernanda de Figueiredo (2023)
The work seeks to understand the experiences under study, weaving elements to understand how ancestral knowledge, through the reconstruction of these black bodies-territory, life stories, knowledge and know-how, has awakened new paradigms in health from the collective memory of the communities. The aim is to study popular community health and the relationship with the Brazilian Association of Popular Community Homeopathy, through the experiences produced by the communities that are part of the Casa do Caminho Project coordinated by Sister Assunta Tacca. This research seeks to analyse how ancestral and decolonial knowledge is combined in the popular community health practices organized through the Casa do Caminho Project, by observing and understanding how the new paradigms in health and their epistemes have been approached, seeking to analyse them in relation to their contributions to the various dimensions that make up integral health. The investigative work is based in the southern region of Rio Grande do Sul, in the municipalities of Pelotas, Canguçu and Rio Grande, involving communities on the urban periphery and in rural areas, among the fourteen accompanied by Sister Assunta. This work involves health professionals, therapists and volunteers and is currently intertwined with the experience of the Brazilian Association of Popular Homeopathy. As for the theoretical and methodological perspective, the study is defined as qualitative research, with a bibliographical and documentary survey, a review of legislation and field research. It is based on the conceptual foundations of writing in terms of interviews, listening and participant observation, with the aim of producing narratives in relation to the composition of this knowledge. The construction of knowledge is inspired by cosmosensation and cosmoperception, highlighting the different meanings that make up the healing processes and emerge from the ecology of knowledge and the phenomenology of perception that characterize the experiences lived. It identifies the sociological absences and the possibilities for knowledge to emerge through popular health education policies, integrative and complementary health practices, technical assistance and rural extension policies, rural and forest peoples, the black population, medicinal plants and herbal medicines. These possibilities are translated into interculturality, bringing together different cosmologies transmitted by these care practices. The results of the research identify the need to articulate the common guidelines that underpin rural extension policies and their agroecological principles with policies on integrative practices and popular education in health, strengthening them in decision-making spaces on the recognition of masters of knowledge, bringing together different policies, knowledge and cosmologies in favor of integrative health that strengthens life, nature and a planetary cosmoethics.